2020
DOI: 10.4093/dmj.2020.0105
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Diabetes on Clinical Outcomes in Patients with Coronavirus Disease 2019: A Retrospective Cohort Study

Abstract: Background To determine the role of diabetes mellitus (DM) in the coronavirus disease 2019 (COVID-19), we explored the clinical characteristics of patients with DM and compared risk factors such as age, glycemic control, and medications to those without DM. Methods This was a retrospective cohort study of 117 confirmed patients with COVID-19 which conducted at a tertiary hospital in Daegu, South Korea. The primary outcome was defined as the severe and critical outcome (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 26 publications
4
72
0
3
Order By: Relevance
“…Interestingly, multivariate logistic regression analysis revealed that an age of ≥70 years and a high serum LDH level significantly predicted mortality among hospitalized COVID-19 patients with diabetes. Similarly, other studies have reported that an age of >60 years is a major predictor of disease severity and mortality among diabetic COVID-19 patients [16,17]. A growing body of literatures supported an age of ≥70 years' patients with COVID-19 had incremental severity and mortality than younger ones [23,27].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, multivariate logistic regression analysis revealed that an age of ≥70 years and a high serum LDH level significantly predicted mortality among hospitalized COVID-19 patients with diabetes. Similarly, other studies have reported that an age of >60 years is a major predictor of disease severity and mortality among diabetic COVID-19 patients [16,17]. A growing body of literatures supported an age of ≥70 years' patients with COVID-19 had incremental severity and mortality than younger ones [23,27].…”
Section: Discussionmentioning
confidence: 74%
“…Several systematic reviews and meta-analyses [15,16], cohort [14,17], case-control [12], and cross-sectional studies [16,18] have demonstrated that diabetic patients with COVID-19 are at considerably greater risk of mortality and of developing more severe disease than COVID-19 patients without diabetes. However, it was reported in a recent study that diabetes had no effect on the prognosis of COVID-19 patients but was negatively associated with clinical outcomes [19], which indicated studies are needed to narrow gaps in our understanding of the disease, and thus, aid decision-making by health care providers and administrators.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality among patients with diabetes was 19.3%, whereas previous studies have reported rates from 7.3% to 81.3%. 25 26 27 28 29 Several factors such as an impaired immune system, a pre-existing proinflammatory state, direct pancreatic damage, and dysregulation of ACE2 signaling have been suggested to contribute to the association between diabetes and COVID-19. 30 31 Cancer patients tend to be immunocompromised and at increased risk of serious COVID-19-related events.…”
Section: Discussionmentioning
confidence: 99%
“…These two university hospitals are the largest among the four designated explicitly for patients with severe COVID-19 transferred from other facilities or hospitals in Daegu. The diagnosis of COVID-19 was made with positive results by real-time reverse transcription polymerase chain reaction assay for SARS-CoV-2 in upper respiratory specimens (nasopharyngeal and oropharyngeal swab), with or without a lower respiratory specimen (sputum) [12]. Based on clinical judgments, patients who were transferred because their medical conditions required prompt intensive monitoring and care in the early stages of the outbreak were investigated.…”
Section: Study Design and Participantsmentioning
confidence: 99%